High diversity of Ocellularia (Ascomycota: Graphidaceae) in the Colombian Llanos, including two species new to science - Peláez, Rouchi N.; Moncada, Bibiana; Lücking, Robert (Phytotaxa, 2014)
An inventory of crustose epiphytic lichens in gallery forests dominated by the Moriche palm, Mauritia flexuosa, in the Colombian Llanos revealed a high diversity of species of the genus Ocellularia s.str. Thirteen species were identified in the material, some of them previously known from very few collections only. Two species are new to science and ten are new records for Colombia. The two new species are O. umbilicatoides Peláez, Moncada & Lücking, differing from O. umbilicata in the presence of a (carbonized) columella, and O. usnicolor Peláez, Moncada & Lücking, differing from O. psorbarroensis in the carbonized columella and dark brown to carbonized excipulum and the mottled white-yellowish green thallus. We also revised the nomenclature of species of Ocellularia previously listed for Colombia and propose the new combination Ocellularia dodecamera (Nyl.) Peláez, Moncada & Lücking.